A COMPARATIVE STUDY OF OPTICAL BIOMETRY AND IMMERSION A-SCAN ULTRASOUND IN PATIENTS UNDERGOING PHACOEMULSIFICATION WITH FOLDABLE INTRAOCULAR LENS IMPLANTATION SURGERY - DONGARE, SUMIT DILIP; JOSHI, AJIT KAMALAKAR; PACHAURI, NISARG (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study was to compare optical biometry with immersion A-scan ultrasound biometry in terms of axial length (AL) and post-operative refractive error by assessing 1-month post-operative refraction in patients undergoing phacoemulsification with foldable intraocular lens (IOL) implantation surgery. Methods: The study was carried out in the Ophthalmology Department of Bharati Vidyapeeth (Demeed to be University) Medical College and Hospital Sangli, from November 2019 to April 2021. A total of 60 eyes of 60 patients were included in the study. All patients underwent both techniques of biometry, namely, optical and immersion A-scan biometry. Mean AL was calculated and compared between the two methods. Then patients were divided into two groups: Group A and Group B; randomization was done on the basis of odd and even numbers. All patients underwent phacoemulsification with foldable IOL implantation surgery and followed up on 1 week and then on 1 month. All patients were operated by single surgeon and a single technique was used. Actual post-operative refractive error, that is, mean of spherical equivalent was compared between two groups on 1-month follow-up. Results: At 1-month follow-up, actual post-operative refractive error was obtained after calculating spherical equivalent for all the patients and we found that, the mean of actual post-operative refractive error for Group A was higher (−0.371±0.24 D) compared to Group B (−0.264±0.16 D) and the comparison was statistically significant (p=0.049). Conclusion: Optical biometry is slightly more accurate than ultrasound biometry, in terms of accuracy and reproducibility of the IOL power calculation, but ultrasound biometry is adequate in case optical biometry is unavailable.